'We thought you were undercover, here to inspect us' – Some of the Challenges of Ethnographic Fieldwork in Schools. (1st November 2016) - Hodgkin, Kieran; Fleming, Scott; Beauchamp, Gary; Bryant, Anna
This paper provides an insight into the challenges associated with conducting ethnographic fieldwork in a primary school and a secondary school in south Wales. Drawing on personal reflections and experiences, it provides an account of the lessons learnt. Themes include gaining access, role selection, establishing trust, developing relationships and role conflict. More specifically, the differences associated with conducting research in a primary and secondary school are identified, whilst highlighting the fragile nature of pupil-centred research.